Perubahan Plastisitas dan Permaebilitas Tanah Lempung (CH) terhadap Penambahan Semen dan Limbah BAFA - Syawal Satibi; Zega, Lala Monang Robert Christian; Soewignjo Agus Nugroho (Jurnal Teknologi dan Rekayasa Sipil, 2022)
High Plasticity Clay (CH) soils have poor material characteristics, such as large shrinkage which results in high plasticity so that soil improvement is required using cement and coal waste is added (bottom ash and fly ash). The purpose of adding the mixture is to see its effect on changes in the properties of soil plasticity and permeability. BAFA variation is 4%, 8%, 12% and 16%, cement variation is 3% and 5%. Atterberg limit and soil permeability testing is carried out on ripening day 0.7 and 28 days. The test results show changes in the value of Plasticity Index (Plasticity Index) or the value of PI and the value of k (constant) in the soil permeability test that has been added to the mixed material. Based on the results of the atterberg limit test, there was a decrease in the value of the soil plasticity index (PI) and the liquid limit value (LL) while the plastic limit (PL) experienced an increase in value along with the increase in cement content and BAFA waste, while in the soil permeability test it was known that the original soil sample was more difficult to penetrate water compared to soil samples that have been mixed with cement and BAFA waste.